Dealing with Law in Migration Control: The Powers of Street-level Bureaucrats at French Consulates. (June 2014) - Alpes, Maybritt Jill; Spire, Alexis
This article examines how street-level bureaucrats within migration control use their scope for discretionary powers. On the basis of two ethnographic studies of French consulates in Yaoundé and Tunis, we argue that state agents' practices are significantly shaped by organizational constraints such as how decision-making processes are organized and the bureaucratic habitus, including the fear of fraud. Like other street-level bureaucrats, consular agents are able to draw on legal frameworks in a flexible and instrumental manner. Yet, in the field of migration policy, their scope for discretionary decision making is wider and influenced by their belief that they are acting to defend the national interest. This gives a more political dimension to the way such agents deal with law.